2016
DOI: 10.1123/ijsnem.2015-0186
|View full text |Cite
|
Sign up to set email alerts
|

Does Short-Term High Dose Probiotic Supplementation Containing Lactobacillus casei Attenuate Exertional-Heat Stress Induced Endotoxaemia and Cytokinaemia?

Abstract: The study aimed to determine if short-term high dose probiotic supplementation containing Lactobacillus casei (L.casei) attenuates the commonly reported exertional-heat stress (EHS) induced endotoxinaemia and cytokinaemia. Eight endurance trained male volunteers (mean± SD: age 26 ± 6 y, nude body mass 70.2 ± 8.8 kg, height 1.75 ± 0.05 m, VO2max 59 ± 5 ml·kg-1·min-1) completed a blinded randomized cross-over design, whereby oral ingestion of a commercially available probiotic beverage containing L.casei (volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 0 publications
4
102
2
1
Order By: Relevance
“…Collectively, these results support the contention that a multistrain pro/prebiotic intervention maintains tight junction stability, potentially through interference with phosphorylation processes. Although this supports previous findings [26,48], such strategies may only apply to chronic interventions, as recent research has demonstrated no impact of acute (7 days) probiotic use on endotoxin levels following endurance exercise at 60%VO 2 max under ambient or heat-stressed conditions [49]. …”
Section: Discussionsupporting
confidence: 89%
“…Collectively, these results support the contention that a multistrain pro/prebiotic intervention maintains tight junction stability, potentially through interference with phosphorylation processes. Although this supports previous findings [26,48], such strategies may only apply to chronic interventions, as recent research has demonstrated no impact of acute (7 days) probiotic use on endotoxin levels following endurance exercise at 60%VO 2 max under ambient or heat-stressed conditions [49]. …”
Section: Discussionsupporting
confidence: 89%
“…Similarly, 14 weeks of multi‐species probiotics (10 10 CFU/d) had no effect on exercise‐induced cytokinaemia in response to 90 minutes of cycle ergometer exercise using an incremental high intensity protocol . A more recent study observed that oral ingestion of a commercially available probiotic beverage containing L.casei (volume equivalent for ×10 11 CFU/d) for seven consecutive days before 2 hours of running at 60% VO 2max in hot ambient conditions (34.0°C) resulted in a substantially greater endotoxaemia and cytokinaemia during the recovery period, compared with placebo . Thus, evidence that probiotic might be beneficial in preventing or attenuating exercise‐induced gastrointestinal syndrome is limited, and may actually contribute as an exacerbating factor.…”
Section: Prevention Strategiesmentioning
confidence: 97%
“…Maintaining euhydration during ultra‐marathon competition may be an important factor in attenuating exercise‐induced endotoxaemia and cytokinaemia . Indeed, participants who had an exercise‐induced body mass loss of >2% and a plasma osmolality >300 mOsmol/kg showed higher average circulating endotoxin concentrations compared with those who maintained euhydration with ad libitum water intake during 2 hours running at 60% VO 2max in hot ambient condition (34°C) . Attention must also be given to avoid over‐hydration during exercise, considering exercise‐associated hyponatraemia has been linked to gastrointestinal symptoms, particularly nausea and regurgitation .…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Participants were free to consume their normal diet throughout the experimental procedure (Costa et al 2005, Gill et al 2016. Dietary intake and exercise training were monitored for three days before GC1 and throughout the gut-training protocol.…”
Section: Preliminary Measuresmentioning
confidence: 99%
“…Participants reported to the laboratory at 08:00 h after consumption of a standardised low fibre and FODMAP breakfast (2.2 MJ, 107 g carbohydrate, 16 g protein, and 3 g fat) with 400 ml of water (consumed at 07:00 h) (Gill et al 2016). Within 30 min of the initial gut-challenge trial (GC1), participants were asked to void before body mass measurements, provide a breath sample into a 250 ml breath collection bag (Wagner Analysen Technick, Bremen, Germany), and complete a self-reported gastrointestinal symptom assessment tool.…”
Section: Preliminary Measuresmentioning
confidence: 99%